Pengeringan Tembakau dengan Sistem Hybrid - Muhammad Nadjib, Dwi Aries Himawanto , (Jurnal Semesta Teknika, 2013)
Productivity of tobacco crop may be affected by several factors, one of which is the weather that can influence the tobacco drying process. Providing a customized tobacco dryer may help solving these problems. The study begins by designing a solar energy and biomass (tobacco stem waste) combustion followed by manufacturing and data collection of dryer performance. It can be concluded that the dryer for 140 minutes can reduce the moisture content of fresh tobacco leaves to Â 64%.